Calcification of the abdominal aorta is an under-appreciated cardiovascular disease risk factor in the general population - Sethi, Anurag; Taylor, D. Leland; Ruby, J. Graham; Venkataraman, Jagadish; Sorokin, Elena; Cule, Madeleine; Melamud, Eugene (Frontiers in Cardiovascular Medicine, 2022)
Calcification of large arteries is a high-risk factor in the development of cardiovascular diseases, however, due to the lack of routine monitoring, the pathology remains severely under-diagnosed and prevalence in the general population is not known. We have developed a set of machine learning methods to quantitate levels of abdominal aortic calcification (AAC) in the UK Biobank imaging cohort and carried out the largest to-date analysis of genetic, biochemical, and epidemiological risk factors associated with the pathology. In a genetic association study, we identified three novel loci associated with AAC (FGF9, NAV9, and APOE), and replicated a previously reported association at the TWIST1/HDAC9 locus. We find that AAC is a highly prevalent pathology, with 1 in 10 adults above the age of 40 showing significant levels of hydroxyapatite build-up (Kauppila score > 3). Presentation of AAC was strongly predictive of future cardiovascular events including stenosis of precerebral arteries (HR 1.5), myocardial infarction (HR 1.3), ischemic heart disease (HR 1.3), as well as other diseases such as chronic obstructive pulmonary disease (HR 1.3). Significantly, we find that the risk for myocardial infarction from elevated AAC (HR 1.4) was comparable to the risk of hypercholesterolemia (HR 1.4), yet most people who develop AAC are not hypercholesterolemic. Furthermore, the overwhelming majority (98%) of individuals who develop pathology do so in the absence of known pre-existing risk conditions such as chronic kidney disease and diabetes (0.6% and 2.7% respectively). Our findings indicate that despite the high cardiovascular risk, calcification of large arteries remains a largely under-diagnosed lethal condition, and there is a clear need for increased awareness and monitoring of the pathology in the general population.